2019
DOI: 10.1021/acs.chemmater.8b04285
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Expansion Framework for the Sr(Ti1–xFex)O3–x/2 (0 < x < 1) Mixed Ionic Electronic Conductor: Properties Based on Realistic Configurations

Abstract: Several mixed ionic/electronic conductors (MIECs) used as fuel or electrolysis cell electrodes may be thought of as solid solutions of perovskite oxides and ordered oxygen vacancy compounds. For example, the model MIEC SrTi 1−x Fe x O 3−x/2+δ (STF) can be described as a mixture of the perovskite SrTiO 3 and the brownmillerite Sr 2 Fe 2 O 5 that can accommodate some degree of oxygen offstoichiometry δ. The large configurational space for these nondilute, disordered mixtures has hindered atomic scale modeling, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…13 Such disagreement between the model and the measurement results was explained by oxygen vacancy ordering, typical of highly nonstoichiometric SrFeO 3– δ (ref. 13) as well as similar oxides such as SrFe 1– x Ti x O 3– δ , 141,142 impacting ε chem values. This conclusion is qualitatively supported by the DFT simulation results, showing increasing oxygen vacancy polaron size with increasing δ in Sr 1– x La x FeO 3– δ due to the vacancy ordering.…”
Section: Various Models and Approaches To Understand The Chemical Exp...mentioning
confidence: 99%
“…13 Such disagreement between the model and the measurement results was explained by oxygen vacancy ordering, typical of highly nonstoichiometric SrFeO 3– δ (ref. 13) as well as similar oxides such as SrFe 1– x Ti x O 3– δ , 141,142 impacting ε chem values. This conclusion is qualitatively supported by the DFT simulation results, showing increasing oxygen vacancy polaron size with increasing δ in Sr 1– x La x FeO 3– δ due to the vacancy ordering.…”
Section: Various Models and Approaches To Understand The Chemical Exp...mentioning
confidence: 99%
“…However, recently, it was shown that the SQS configurations are not ground states, as more stable configurations for disordered systems were identified via cluster expansion (CE) Monte Carlo (MC) simulations. 16 Yet, it remains unclear whether the reported model accuracy of CE is sufficient for configurational optimization. For example, considering a large supercell with 300 atoms, which is typically needed to mimic the randomness of disordered perovskites, 15 the model's prediction error of 5 meV/atom would lead to the deviation of the estimated total energy of 1.5 eV.…”
Section: Introductionmentioning
confidence: 99%
“…These SQS configurations were found to satisfactorily reproduce many material properties. However, recently, it was shown that the SQS configurations are not ground states, as more stable configurations for disordered systems were identified via cluster expansion (CE) Monte Carlo (MC) simulations . Yet, it remains unclear whether the reported model accuracy of CE is sufficient for configurational optimization.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we use alloy cluster expansions (CEs) fitted to DFT to describe the energetics of the system ranging from 0% to 50% Au in Pd and in the full range from no hydrogen to 100% hydrogen (i.e., 1 H atom per 1 Au or Pd atom). This approach, which has been successfully applied to similar materials in the past [30][31][32][33][34], allows for very fast evaluation of the energy of a system with hundreds of atoms with an accuracy approaching that of DFT. Using Monte Carlo (MC) simulations, we can elucidate the thermodynamics and, in particular, study how chemical order evolves under different circumstances.…”
Section: Introductionmentioning
confidence: 99%